Derivation Mathematical Equations for Future Calculation of Potential Evapotranspiration in Iraq, A Review of Application of Thornthwaite Evapotranspiration - Al-Sudani, Hussein Ilaibi Zamil (Iraqi Journal of Science, 2019)
In any natural area or water body, evapotranspiration is one of the important outcomes in the water balance equation. As a significant method and depending on monthly average temperature, estimating of potential Evapotranspiration depending on Thornthwaite method was adopted in this research review. Estimate and discuss evapotranspiration by using Thornthwaite method is the main objectives of this research review with considerable details as well as compute potential evapotranspiration based on climatologically data obtained in Iraq. Temperature - evapotranspiration relationship can be estimated between those two parameters to reduce cost and time and facilitate calculation of water balance in lakes, river, and hydrogeological basins. The relationship was obtained using Thornthwaite method in Iraq by dividing the area into seven sectors according to geographic latitude. Each sector has multi meteorological stations where thirty two stations were used with different periods of records. A mathematical relationship was obtained between mean temperature and corrected potential evapotranspiration with (97.45) to (99.84) coefficient of determination. The mean temperature has a decreasing pattern from southern east towards northern west of Iraq affected by Mediterranean Sea climate conditions, while corrected potential evapotranspiration has the opposite direction regarding increased value because of a direct relationship with temperature.